Ross Island recreational walking tracks: relationships between soil physiochemical properties and track usage. (July 2015) - O'Neill, Tanya A.; Balks, Megan R.; López-Martínez, Jerónimo
ABSTRACT The objective of this research was to determine the number of people using the Ross Island recreational walking tracks, and to examine the relationships between the number of users, track morphological characteristics, and soil physiochemical properties. Infrared track counters provided 2-years of data on five walking tracks on the island. Track width and track incision were measured and soil sampling in the vicinity of the track counter and an adjacent control site was undertaken. Between January 2009 and January 2011 5084 passes were recorded on the Scott Base to McMurdo Station walking track, 2842 on the Wind Vane Hill walking track, 3561 on the Round Observation Hill walking track, 10936 on the Up Observation Hill track, and 693 on the Crater Hill summit walking track. There were more users on all tracks in the 2010–2011 summer season than the 2009–2010 summer season. The highest frequency of visitors occurred on Sundays during the summer (November to January). There was no relationship between the number of passes on the track and the measured impact indicators. This indicates that higher usage of a formed track had little cumulative impact. Track width and incision were related to the slope of the terrain, with tracks traversing flatter areas generally wider (R2 = 0.85) and less incised (R2 = 0.96), than those traversing steeper hillsides. There were no significant differences between tracks and control samples in soil pH, soil EC, organic C, total N, and total P. However, soil bulk density was higher in the walking tracks than adjacent control areas (p < 0.05).